2014
DOI: 10.11648/j.ajce.20140204.11
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Steel Fibers on the Behavior of Light Weight Concrete Made from Crushed Clay Bricks

Abstract: The purpose of this study is to investigate the effects of steel fibers on some properties of light weight concrete. The coarse aggregate used in this study made from crushed clay bricks. Four proportions of steel fibers are used (0.25%, 0.5%, 0.75%, and 1%) by volume of concrete, in addition, to reference mix (without steel fibers). The density obtained from experimental work was 1812 Kg/m³. The results showed that, in general, the adding of steel fibers led to increase the compressive strength of light weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…According to [14] and [16], fine aggregate should not contain more than 5% sludge and not contain organic which can damage concrete. [17] A normal weight washed sand with a (4.75mm) maximum size is used as fine aggregates its use is to fill the space between coarse aggregates and provide discomfort. The graphic of the test results for fine aggregate grains is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to [14] and [16], fine aggregate should not contain more than 5% sludge and not contain organic which can damage concrete. [17] A normal weight washed sand with a (4.75mm) maximum size is used as fine aggregates its use is to fill the space between coarse aggregates and provide discomfort. The graphic of the test results for fine aggregate grains is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The flexural ultimate strength for a thin-section beam was assessed with a third point loading (TPL) test [ 12 , 13 , 14 , 15 , 16 ]. The constant displacement rate used in this experiment was 2 mm × min −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Zinkaah [ 13 ] found that the water absorption of lightweight concrete with steel fibers exceeded its counterpart lacking fibers, increasing from 1.31% to 9.24% when the volume of steel fibers increased from 0 to 1%. Moreover, Jhatial et al [ 14 ] elucidated the effect of hooked-end steel fibers with lengths of 25 mm and diameters of 0.5 mm on the compressive and flexural strengths of the composite and reported that a 3% steel fiber fraction reinforcement resulted in the highest compressive strength of 31.46 MPa, which was ~18.27% higher than that of the control sample; its flexural strength was 6.16 MPa, which was ~51.72% higher than that of the control sample.…”
Section: Introductionmentioning
confidence: 99%
“…Including fibers with an aspect ratio of 65 causes a slight reduction in compressive strength for other concrete mixes ( WH2 and WH3). This could be attributable to the formation of air pores and voids in these mixes, both of which lower compressive strength [32].…”
Section: Compressive Strengthmentioning
confidence: 99%